Perancangan Kampanye Sosial Sopan Santun Berkomunikasi Mahasiswa Dengan Dosen Menggunakan Gadget - Apsari Dj. Hasan; Risti Puspita Sari Hunowu (STEKOM PRESS, 2023)
Manners or manners are one of the most important and influential things in social life. For example, when a student talks to someone with a cell phone or gadget. So to avoid unwanted activities when a student contacts the lecturer via gadget, a standard is made regarding the rules for communicating through gadgets properly and politely. This research generally discusses the problem of students' lack of understanding about the rules of communicating with lecturers using gadgets. Based on these problems, a design was made that aims to provide information and understanding to students about the rules for communicating between students and lecturers using gadgets. In this design, the media that will be used as a media campaign is a poster. This study uses observations on how students communicate with lecturers using gadgets as well as literature studies on the theory of visual design communication media campaigns in the form of posters. With the results of research based on the aspects and theories used, it is hoped that it can enrich the repertoire of visual communication science in the design of social campaigns as a reference for subsequent studies. Keywords: social campaigns, gadgets, posters.